2015
DOI: 10.1515/zpch-2014-0658
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Diffusion in Ion-Beam Sputtered Amorphous LiAlO2

Abstract: Abstract:We investigated lithium self-diffusion in amorphous lithium aluminate (LiAlO 2 ) layers between room temperature and 473 K. For the experiments, amorphous 6 LiAlO 2 (30 nm)/ 7 LiAlO 2 (1200 nm) isotope hetero-structures were deposited by ion-beam sputtering on sapphire substrates. Diffusion profiles were analysed by secondary ion mass spectrometry (SIMS). The results show that the diffusivities obey the Arrhenius law with an activation enthalpy of (0.94±0.02) eV. This is not much different to the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
3
8
1
Order By: Relevance
“…The Li diffusivities of the nanocrystalline -LiAlO 2 samples reported in the literature [20] are also higher than those presented here for the microcrystalline form, and the activation energy varies from 0.78 to 1.14 eV depending on the milling time. So the overall diffusion behavior in different structural forms (single crystalline, microcrystalline, nanocrystalline and amorphous) seems to be qualitatively similar to that in the extensively studied model system LiNbO 3 [32,35,36], although the diffusivity enhancements in the amorphous forms in the two systems differ quantitatively [31]. To sum up, the diffusion results obtained here on microcrystalline -LiAlO 2 are shown in Figure 8.…”
Section: At Low Temperatures Thesupporting
confidence: 67%
See 1 more Smart Citation
“…The Li diffusivities of the nanocrystalline -LiAlO 2 samples reported in the literature [20] are also higher than those presented here for the microcrystalline form, and the activation energy varies from 0.78 to 1.14 eV depending on the milling time. So the overall diffusion behavior in different structural forms (single crystalline, microcrystalline, nanocrystalline and amorphous) seems to be qualitatively similar to that in the extensively studied model system LiNbO 3 [32,35,36], although the diffusivity enhancements in the amorphous forms in the two systems differ quantitatively [31]. To sum up, the diffusion results obtained here on microcrystalline -LiAlO 2 are shown in Figure 8.…”
Section: At Low Temperatures Thesupporting
confidence: 67%
“…Secondary ion mass spectrometry (SIMS) showed a similar activation energy of 0.9 eV for amorphous LiAlO 2 [31]. As expected, the values of diffusion coefficients occurred to be higher in the amorphous material than in the microcrystalline form despite the similar activation energies.…”
Section: At Low Temperatures Thesupporting
confidence: 63%
“…The samples were characterized between room temperature and 473 K [83]. Diffusion profiles were analysed by SIMS.…”
Section: Lithium Aluminatementioning
confidence: 99%
“…The authors explained the difference in barrier energy between these two forms of sample with the presence in larger concentrations of defects and vacancies in the powder sample than in the single crystal. The study in amorphous LiAlO2 from room temperature and 473 K showed 37 that the lithium diffusivity obeys the Arrhenius law with an activation energy of 0.94 eV and significantly higher Li diffusion coefficient 3.6 ×10 -15 m 2 /sec at 473K , which is three order of magnitude higher than in crystalline phase (~10 -18 m 2 /sec) at same temperature 28 . A study on disordered γ-LiAlO2 showed that the introduction of structural disorder significantly enhances the Li ion conductivity in γ-LiAlO2 26 . Several new solid superionic electrolytes have been discovered in which the diffusion mechanism is found to be strongly correlated with the rotational dynamics of constituent polyhedra 38 .…”
Section: Introductionmentioning
confidence: 95%